Pembangunan Sistem Informasi Keuangan Berbasis Website Menggunakan Metode Prototyping (studi Kasus: Rumah Sakit Bakti Timah Karimun) - Rahma Mawaddah Febriani; Muhammad Ihsan Zul (Politeknik Caltex Riau, 2021)
Bakti Timah Karimun Hospital Financial System is a management information system in Bakti Timah Karimun hospital. The purpose of this research is to change the Financial System at Bakti Timah Karimun Hospital from a manual system using paper to a website-based Financial System and to implement a website-based Financial System in the preparation of financial statements at Bakti Timah Karimun Hospital. This research resulted in the Hospital Financial System being built using prototype methods and CI framework at Bakti Timah Karimun Hospital. The construction of the system system was completed on 2 iterations and the work of the system for approximately 3 months. This system was built according to the needs of Bakti Timah Karimun Hospital. The system built can help bakti Timah Karimun Hospital in the process of managing hospital finances. Keywords: Bakti Timah Karimun Hospital, Financial System, Prototype, CI Framework.